Seven Dickensian lessons for tough times - Sanz Barajas, Jorge (Razón y fe, 2018)
This year is the two hundredth anniversary of the great Charles Dickens’ birth (1812-1870). His versatile and humanistic work remains as alive as ever. The characters presented in his novels and tales still reflect our dreams, aspirations, tragedies and hopes. Reading any of his works approaches us to a classic and at the same time it shows us that the life and the existence of the most humble can be lived as a community through humor, dignity, heart, loyalty, realism and above all, with hope.
Keywords: Charles Dickens; 19th century; humor; dignity; realism and hope